The global distribution of gains from globalization - Valentin Lang; Marina M. Tavares (The Journal of Economic Inequality, 2023)
Global interpersonal inequality is increasingly driven by inequalities within countries while the role of inequality between countries diminishes. Is this due to globalization? To answer this question, we use comprehensive global panel data at the country-decile-group level for the past half century and exploit the geographic diffusion of liberalization policies to identify the effect of globalization. Across countries, we find that income gains are substantial for countries at early stages of the globalization process, but the `marginal returns to globalization' diminish as globalization rises, eventually becoming insignificant for the most globalized countries. Within countries, gains from globalization are largest for the richest ten percent of national income distributions, resulting in substantial increases in national income inequalities. A simple quantitative model is consistent with these empirical results. Over the past half century, globalization has promoted a dual trend of income convergence across countries and income divergence within countries.
Keywords: F63; O15; O47; 300; Global inequality; Globalization; Growth